WORKSHOP PENULISAN ARTIKEL DI MEDIA MASSA BAGI AKTIVIS DAKWAH PERSYARIKATAN AISYIYAH SE-KARESIDENAN PEKALONGAN - Fahrudin Eko Hardiyanto (LPPM Universitas Pekalongan, 2020)
Writing articles on mass media for missionary activists is a very important and strategic activity to be able to communicate the results of thoughts, ideas, alignments, attitudes, solutions, and the like to the wider community. The aim of community service to write this article is to improve the ability to write articles for the preaching activist Persyarikatan Aisyiyah in the Pekalongan Residency. There are 5 stages of activity in this article writing workshop, namely (1) Brainstorming, (2) Clustering (grouping of materials), (3) Jotting (rough writing), (4) Rewriting (re-writing), and (5) Finishing (final settlement). Based on the evaluation of the implementation of community service activities, it appears that there has been an increase in the ability to write articles through workshops. This can be seen from the enthusiasm of the participants during the training activities and the results of the writing process that occurred during this dedication which showed an increase in the ability to write articles for Aisyiyah mothers in the Pekalongan Residency.Keywords: article, community service, Aisyiyah